Tourism development and tourism impacts in Kilim Geopark, Langkawi: How local community perceive on economic impact - Ahmad, Nurul Azwa; Shuib, Ahmad; Ramachandran, Sridar; M. A., Syamsul Herman (2013)
This paper examines how tourism development of Langkawi into a popular tourist destination and the impacts to the local economy also generating local community income. In the second phase of the development project known as "Langkawi Tourism Blueprints". Langkawi is made into a nature ecotourism destination of international standard and to emphasizes the shift towards content development rather than infrastructure. This transformation, especially in the Kilim Karst Geopark, will being about economic impacts where the government hopes will get local supports.